1993
DOI: 10.1016/0014-5793(93)81612-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome d induction in Escherichia coli growing under unfavorable conditions

Abstract: Growth of .E. coli in the presence of the protonophorous uncoupler pentachlorophenol is shown to strongly enhance levels of cytochrome d, a putative Na+-motive oxidase. This effect was found to be arrested by chloramphenicol and stimulated by high Na+ concentration in the growth medium. The induction of cytochrome d takes place in a mutant deficient in the FoF, ATP-synthase but does not occur in mutants deficient in either of two different components of the Arc system. Similar relationships were revealed when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…ArcA is the transcriptional regulator, and ArcB is a transmembrane protein that contains receiver and transmitter domains. Signals recognized by ArcB, thought to be membrane potential or metabolites generated during anaerobic growth, may activate the system (4,20,21,(26)(27)(28). Recently, Georgellis et al reported that the redox signals for the ArcAB system are quinones which are membrane-associated electron carriers (21).…”
Section: Discussionmentioning
confidence: 99%
“…ArcA is the transcriptional regulator, and ArcB is a transmembrane protein that contains receiver and transmitter domains. Signals recognized by ArcB, thought to be membrane potential or metabolites generated during anaerobic growth, may activate the system (4,20,21,(26)(27)(28). Recently, Georgellis et al reported that the redox signals for the ArcAB system are quinones which are membrane-associated electron carriers (21).…”
Section: Discussionmentioning
confidence: 99%
“…As well as adapting to low oxygen conditions, expression and membrane content of cytochrome bd-I has been shown to increase in response to a variety of stresses, including high temperature (Delaney, Wall, & Georgopoulos, 1993;Wall et al, 1992), high pH (Avetisyan, Dibrov, Semeykina, Skulachev, & Sokolov, 1991), high pressure (Tamegai et al, 2005) and the presence of protonophore-uncouplers (Avetisyan et al, 1991;Bogachev, Murtazina, Shestopalov, & Skulachev, 1995;Bogachev, Murtazina, & Skulachev, 1993). Also, induction of cytochrome bd-I by heat shock and loss of PMF is dependent upon the ArcAB two-component system (Wall et al, 1992).…”
Section: Regulation Of the Cyo And Cydab Operonsmentioning
confidence: 97%
“…thermoautotrophicum [ 151. In this context it should be mentioned that the requirement of a high concentration of Na' for induction of the Enterococcus hirae Na'-ATPase and for the Na'-motive oxidase of Escherichia coli was reported [22,23]. In different methanogenic bacteria the existence of a sodium cycle has been suggested [9,24,25].…”
Section: P Smigcin Et Al Ifebs Letters 349 (1994) 424428mentioning
confidence: 99%